Essentials of anatomy - Singh, Inderbir (Jaypee Brothers Medical Publishers, 2009)
This book is a condensed version of the author's three volume Textbook of Anatomy. It has been produced in response to the reduced time available for the study of Anatomy consequent to the decision of the Medical Council of India to reduce the period of the first professional MBBS course from 18 months to 12 months. Incorporates all the relevant and necessary information to enable the students to have a sufficient knowledge of Anatomy. Contains 6 parts divided into Upper Extremity, Lower extremity, Thorax, Abdomen and Pelvis, Head and Neck, and central nervous system